2016
DOI: 10.1021/acs.est.6b00712
|View full text |Cite
|
Sign up to set email alerts
|

Sample Enrichment for Bioanalytical Assessment of Disinfected Drinking Water: Concentrating the Polar, the Volatiles, and the Unknowns

Abstract: Enrichment methods used in sample preparation for the bioanalytical assessment of disinfected drinking water result in the loss of volatile and hydrophilic disinfection byproducts (DBPs) and hence likely tend to underestimate biological effects. We developed and evaluated methods that are compatible with bioassays, for extracting nonvolatile and volatile DBPs from chlorinated and chloraminated drinking water to minimize the loss of analytes. For nonvolatile DBPs, solid-phase extraction (SPE) with TELOS ENV as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(101 citation statements)
references
References 51 publications
2
97
0
Order By: Relevance
“…based on the detected DBPs, with EC IR1.5 values for the individual detected DBPs collected from Stalter et al (2016a) (provided in Table S1). This approach is justified because Stalter et al (2016b) demonstrated that the BEQ chem, volatile stems mainly from known DBPs, though it should be noted that not all known volatile DBPs were analysed in the current study. BEQ bio was also compared with BEQ chem, non-volatile for chemicals with a Henry's Law…”
Section: Contribution Of Volatile and Non-volatile Dbps To The Observmentioning
confidence: 96%
See 2 more Smart Citations
“…based on the detected DBPs, with EC IR1.5 values for the individual detected DBPs collected from Stalter et al (2016a) (provided in Table S1). This approach is justified because Stalter et al (2016b) demonstrated that the BEQ chem, volatile stems mainly from known DBPs, though it should be noted that not all known volatile DBPs were analysed in the current study. BEQ bio was also compared with BEQ chem, non-volatile for chemicals with a Henry's Law…”
Section: Contribution Of Volatile and Non-volatile Dbps To The Observmentioning
confidence: 96%
“…However, this was not observed for the targeted DBPs. Different sample preparation methods were used for chemical analysis and bioanalysis, with sample enrichment for bioanalysis mainly extracting non-volatile and semi-volatile DBPs, while chemical analysis mostly targeted volatile DBPs (Stalter et al 2016b). Therefore, formation of undetected non-volatile or semi-volatile DBPs may explain the increased effect in September.…”
Section: Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Bioluminescence inhibition assays indicate that DBPs in the non-purgeable fraction (in the specific study defined as the total amount of adsorbed organic halogens (AOX) present after purging the sample with nitrogen for 30 minutes) are of higher toxicological relevance than DBPs in the purgeable fraction. 12 In the same study, AOX and a range of known DBPs were analysed. Most of the AOX in the purgeable fraction, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…non-volatile to semi volatile compounds, demonstrating the lack of available information of DBPs in this pool. 12 Recent work summarizing the challenges and opportunities within DBP research points towards the need of finding the key "toxicity drivers" that can explain the observed risk for bladder cancer, so that efforts to minimize exposure focus on the relevant targets. 13 A number of studies have been carried out to analyze the non-volatile fraction of DBPs using nontarget approaches, where some have focused on lab experiments, [14][15][16][17][18] and a few on real waterworks.…”
Section: Introductionmentioning
confidence: 99%